Multiple Fitness Improvements Found after 6-Months of High Intensity Functional Training - Cosgrove, Sarah J. (Sports (Basel), 2019)
While short-term high intensity functional training (HIFT) effects have been established, fitness improvements from program participation exceeding 16 weeks are unknown. This study examined the effectiveness of participation in HIFT through CrossFit. During 2013–2014, fitness performance testing was incorporated into an ongoing university CrossFit program. Participants included 45 adults (23 women, 22 men) with 0–27 months of HIFT experience (grouped into 0–6 months and 7+ months). Participants completed three separate days of assessments across 10 fitness domains before and after participating in the program for six months. For each sex, 2 (Time) × 2 (Group) RANOVA were used for each fitness test. For women, significant Time effects were found for four fitness domains (i.e., flexibility, power, muscular endurance, and strength), and a Group × Time interaction for cardiorespiratory endurance, with the 0–6-month group improving more. For men, significant Time effects were found for flexibility, muscular endurance, and strength. These data provide evidence for multiple fitness improvements after six months of CrossFit participation with greater 1.5 mile run time improvement among women with less experience.